Dissemination of information system technology in Nagari Pakandangan - Dwiny Meidelfi; Rika Idmayanti; Fanni Sukma; Andre F Kasmar; Meri Azmi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
Nagari is a region that has a very important role to encourage its people to innovate both in the economic and technological fields. Technology is available to facilitate various activities in daily life. Nagari is expected to be able to use technology to assist the community in managing information and data in the Nagari. Management and processing of data related to public services in a Nagari are very important. The data is valid information that must be updated regularly. Nagari Pakandangan is located in the Nagari Pakandangan, Enam Linkuang sub-district, Padang Pariaman district, West Sumatra province. In order to improve the quality of human resources in Nagari Pakandangan, a website-based information system was built that can accommodate data or information from the community in Nagari Pakandangan. This activity is carried out in three stages: a) identification of the problem which is carried out as a first step to determine the formulation of the problem that will be useful as a material for the design of the Nagari information system, b) the design of the Nagari information system, c) the development of the Nagari information system.